The Impact of the Cellular Environment and Aging on Modeling Alzheimer's Disease in 3D Cell Culture Models - Hebisch, Matthias; Klostermeier, Stefanie; Wolf, Katharina; Boccaccini, Aldo R.; Wolf, Stephan; Tanzi, Rudolph E.; Kim, Doo Yeon (Advanced Science, 2023)
Creating a cellular model of Alzheimer's disease (AD) that accurately recapitulates disease pathology has been a longstanding challenge. Recent studies showed that human AD neural cells, integrated into three-dimensional (3D) hydrogel matrix, display key features of AD neuropathology. Like in the human brain, the extracellular matrix (ECM) plays a critical role in determining the rate of neuropathogenesis in hydrogel-based 3D cellular models. Aging, the greatest risk factor for AD, significantly alters brain ECM properties. Therefore, it is important to understand how age-associated changes in ECM affect accumulation of pathogenic molecules, neuroinflammation, and neurodegeneration in AD patients and in vitro models. In this review, mechanistic hypotheses is presented to address the impact of the ECM properties and their changes with aging on AD and AD-related dementias. Altered ECM characteristics in aged brains, including matrix stiffness, pore size, and composition, will contribute to disease pathogenesis by modulating the accumulation, propagation, and spreading of pathogenic molecules of AD. Emerging hydrogel-based disease models with differing ECM properties provide an exciting opportunity to study the impact of brain ECM aging on AD pathogenesis, providing novel mechanistic insights. Understanding the role of ECM aging in AD pathogenesis should also improve modeling AD in 3D hydrogel systems.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Alzheimer; hydrogel; neurodegeneration; nonclassical crystallization; synthetic extracellular matrix